AKHLAK BELAJAR PADA SISWA DALAM PANDANGAN QUR`AN SURAH AL-ISRA’ AYAT 23 - Febriyani; Zakariya, Aulif Angga (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
Nowadays, we can see that many people ignore morals in life, from children to teenagers. The development of sophisticated technology, this makes dependence on children. In addition, moral education at school is rarely emphasized and should be instilled in the educational environment as the main basis. Morals are basically determined by the education he received as a child. How very decisive a moral education from the family environment is. The purpose of this study is to discuss the learning morals contained in the Al-Quran letter Al-Isra' verse 23. The type of research used by the author is qualitative research through library research. With a method that is descriptive analysis, which aims to describe objective data, record, and describe the results in this paper, and data collection is carried out primary and secondary. The results obtained in this article related to learning morals in students according to the view of the Qur'an Surah Al-Isra' verse 23 are according to the opinion of the mufassirs there are two commands, namely to glorify Allah and to be devoted to both parents where moral values are contained therein, namely religious values, democratic values, and disciplinary values.